Study on Determination of the Dynamic Rollover Threshold of a Coach Vehicle - Ta, Tuan Hung; Duong, Ngoc Khanh (Old Journal, 2020)
Rollover condition is one of the worst accidents of a coach vehicle that can occur. The casualties in a coach rollover are often at a high rate and severe because of the large number of passengers. The rollover condition of a coach vehicle depends on the behavior of a driver, the road, the structure of vehicles.... The rollover of coach vehicles frequently occurs while directional maneuvering at high forward speed. It is difficult to recognize the rollover risk signals, i.e. the wheel lift-off, especially at high speed. In this paper, a method to determine the dynamic rollover threshold of the coach vehicle is presented by using a fully dynamic model of coach vehicle based on the Multi-body System Method and Newton–Euler equations. The method can be applied as a basis for determining the early warning and controlling thresholds by dynamic models of coach vehicles.